Is equilibrium enough and was Stigler wrong? Value theory in the Böhm-Bawerk / Fisher controversies - Avi J. Cohen (Duke University, Center for the History of Political Economy (CHOPE), 2011)
The interest-rate controversies between Böhm-Bawerk and Fisher have attracted little attention and, in the opinion of most commentators, justifiably so. Böhm-Bawerk and Fisher argue over what appear to be two minor issues – Böhm-Bawerk's claims that his third cause of interest (productivity of roundabout production processes) is independent of his other two subjective causes of interest and that simultaneous equations models involve circular reasoning and fail to provide a "causal" explanation of interest. The issues not only appear unimportant, their resolution seems clear – Böhm-Bawerk was wrong in both cases. Subsequent commentators, including Stigler, have taken Fisher's side, arguing that Böhm-Bawerk "fails to understand some of the most essential elements of modern economic theory, the concepts of mutual determination and equilibrium (developed by the use of the theory of simultaneous equations)." I propose a radically different assessment, arguing that post-1870 debates over the extension of the subjective marginal utility theory of value to production and distribution, coupled with classical elements in Böhm-Bawerk's theories and his "outsider" status as an Austrian, fuelled the Böhm-Bawerk-Fisher controversies. Böhm-Bawerk was reacting to Fisher's gross exaggeration of subjective (versus objective) elements in his interest theory and wanted a causal explanation of prices in addition to well-understood simultaneous determination. Value theory debates explain both Fisher's exaggerations and Böhm- Bawerk's refusal to be satisfied with equilibrium alone.
Keywords: B13; B31; B4; D24; D46; 330; Böhm-Bawerk; Irving Fisher; capital; causation; methodology; Austrian economics; interest theory; Stigler; equilibrium; value theory; price theory